A comparison of holistic, analytic, and part marking models in speaking assessment. (July 2020) - Khabbazbashi, Nahal; Galaczi, Evelina D.
This mixed methods study examined holistic, analytic, and part marking models (MMs) in terms of their measurement properties and impact on candidate CEFR classifications in a semi-direct online speaking test. Speaking performances of 240 candidates were first marked holistically and by part (phase 1). On the basis of phase 1 findings—which suggested stronger measurement properties for the part MM—phase 2 focused on a comparison of part and analytic MMs. Speaking performances of 400 candidates were rated analytically and by part during that phase. Raters provided open comments on their marking experiences. Results suggested a significant impact of MM; approximately 30% and 50% of candidates in phases 1 and 2 respectively were awarded different (adjacent) CEFR levels depending on the choice of MM used to assign scores. There was a trend of higher CEFR levels with the holistic MM and lower CEFR levels with the part MM. Although strong correlations were found between all pairings of MMs, further analyses revealed important differences. The part MM was shown to display superior measurement qualities particularly in allowing raters to make finer distinctions between different speaking ability levels. These findings have implications for the scoring validity of speaking tests.